2003
DOI: 10.1002/bit.10603
|View full text |Cite
|
Sign up to set email alerts
|

Oil/water and pre‐emulsified oil/water (PIT) dispersions in a stirred vessel: Implications for fermentations

Abstract: This study examines dispersions of rapeseed oil (RSO) in water by mechanical agitation under conditions mimicking those found in certain antibiotic fermentations; for example, in the presence of air, antifoam, and finely divided CaCO(3) particles. A problem with residual oil has been reported for such fermentations, and it has been suggested that the use of pre-emulsified oil can reduce this problem. Hence, the dispersion of a pre-emulsified oil produced by the "phase inversion temperature (PIT) method" has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Above the phase inversion temperature range the oil-in-water dispersion changes to a water-in-oil dispersion and as the temperature falls again a fine stable micro-emulsion is formed with very small oil-in-water droplets (diameter, $0.2 lm). This size is significantly smaller than that obtained ($200 to $800 lm) by dispersing RSO by agitation, the actual size depending on the stage of the fermentation (Erler et al 2003). These latter studies also showed that the drop size ($0.3 lm) in the PIT-RSO emulsion (the same as used here) was unaffected by addition to the broth and remained the same throughout the different stages of the fermentation.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…Above the phase inversion temperature range the oil-in-water dispersion changes to a water-in-oil dispersion and as the temperature falls again a fine stable micro-emulsion is formed with very small oil-in-water droplets (diameter, $0.2 lm). This size is significantly smaller than that obtained ($200 to $800 lm) by dispersing RSO by agitation, the actual size depending on the stage of the fermentation (Erler et al 2003). These latter studies also showed that the drop size ($0.3 lm) in the PIT-RSO emulsion (the same as used here) was unaffected by addition to the broth and remained the same throughout the different stages of the fermentation.…”
Section: Introductionmentioning
confidence: 50%
“…Therefore, further process optimisation will be necessary if the predicted benefits from the use of PIT technology during such fermentation processes are to be realised. However, since the properties of the PIT emulsions are largely independent of scale of operation (Erler et al 2003), depending only on the type of surfactant and fermentation process used, it is suggested that the development of optimal feeding regimes for PIT emulsions during laboratory and production scale could lead to a decrease in final residual oil concentration with higher oxytetracycline titres. Further, that by carefully choosing the emulsification mixture so that the surfactants can be metabolised by the microorganism, then subsequent problems in downstream processing could be avoided.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lost of researches had focused on the processing and utilization of rapeseed oil, especially on the deep refining and industrial application in recent years. However, they din's analyze the liquid rheological characteristic of rapeseed oil to elucidate the instruction for the technology parameters of industrial operation [16,17].…”
Section: Introductionmentioning
confidence: 99%